2018
DOI: 10.1104/pp.17.01637
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides Trigger Two Successive Bursts of Reactive Oxygen Species at Distinct Cellular Locations

Abstract: TITLE 6Lipopolysaccharides trigger two successive bursts of reactive oxygen species at 7 distinct cellular locations 8 AUTHORS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 55 publications
2
40
1
Order By: Relevance
“…In Arabidopsis , ROS production during the immune response is mainly achieved by the NADPH oxidase RBOHD 39 . However, a recent report on LPS perception also suggested that long lasting ROS production could originate from chloroplasts 61 . We found that sustained ROS production triggered by unsaturated SRBs was fully dependent on RBOHD demonstrating that a long lasting oxidative burst could also be generated by the membrane bound NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , ROS production during the immune response is mainly achieved by the NADPH oxidase RBOHD 39 . However, a recent report on LPS perception also suggested that long lasting ROS production could originate from chloroplasts 61 . We found that sustained ROS production triggered by unsaturated SRBs was fully dependent on RBOHD demonstrating that a long lasting oxidative burst could also be generated by the membrane bound NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…ROS assays were carried out as described previously (Shang‐Guan et al ., ). Briefly, leaf discs (0.2 cm 2 ) were incubated overnight in a 96‐well plate with water, and 200 mM luminol (Sigma‐Aldrich, Saint Louis, MO, USA), 20 mg/mL horseradish peroxidase (Sigma‐Aldrich, Saint Louis, MO, USA), or 100 nM flg22 (GenScript, Nanjing, China) were then added.…”
Section: Methodsmentioning
confidence: 97%
“…Plants are also able to sense LPS and activate signaling pathways that ultimately lead to an innate immune response that includes reactive oxygen species (ROS) bursts, callose deposition, nitric oxide production, and transcription of defense-related genes [52][53][54]. The mechanisms underlying the recognition of LPS have only recently started to be understood.…”
Section: Animal and Plant Receptors Recognize Lps And Mount An Immunementioning
confidence: 99%